Pengembangan Desain Produk Lampu Sudut Sesuai Keinginan Konsumen - Dewi, Bella Arinta; , Dr. Suranto, MM (2017)
ABSTRACT This research aims to develop a product design corner lights with Quality Function Deployment (QFD) by utilizing the waste from corn cobs at UD. Imam Mohadi Botitan Village, District Teras, Boyolali and expected by the study was able to reduce the environmental waste. This research is a case study done by collecting data through direct observation of spaciousness, interviews, documentation, and questionnaire. The subject of this study is to respondents who appointed and felt able to provide background information on the development of lighting products a corner. Collecting data in this study using questionnaires and interviews to respondents of 30 respondents to the questionnaire both open and closed. The respondents include employees, housing, restaurant or cafe, and hospitality. Quantitative data is processed descriptively, with a statistical test is the test of validity and reliability testing. Results from making matrix house of quality prioritized the most important for product development corner lights are used for lighting the room, the price is affordable for consumers, packaging attractive, easy to install, the promotion of affordable all people, the material is not easily broken / damaged, and LED lights. Matrix house of quality that has been obtained will be used as reference in the development of lighting products made from waste corner corncobs. Keywords: validity, reliability, respondents